Etika dalam Asesmen Psikologi di Bidang Bimbingan dan Konseling: Menjaga Kerahasiaan dan Objektivitas - Mus Shafira Ramadhani Yapono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article discusses the importance of applying ethical principles in psychological assessments conducted in guidance and counseling services. The main focus of this article is on two basic principles, namely confidentiality and objectivity. Through a review of literature from various academic sources in the last five years, this article shows that maintaining the confidentiality of assessment results is an effort to protect the rights of clients, while objectivity is needed to prevent bias in data interpretation. Case studies, practical challenges, and philosophical reflections are also analyzed to show how ethical principles can be implemented in real practice. This article ends with a recommendation that assessment ethics be used as a basis for counselor education and training.